Ergonomic Risks in Pottery Crafting: Impact on Work-Related Fatigue and Musculoskeletal Disorders - Anastasya Hannie Wuryanie; Tri Martiana; Indriati Paskarini; Widarjanto (Poltekkes Kemenkes Surabaya, 2025)
Pottery workers frequently work in non-ergonomic conditions, including awkward postures and repetitive movements. These factors not only have an impact on workers' productivity and well-being but also contribute to long-term occupational health problems. This study aims to evaluate the ergonomic risk factors in pottery crafting and their impact on the incidence of MSDs and fatigue in Karanganyar Village. A cross-sectional design was employed, involving 43 pottery crafters selected randomly. Ergonomic risk factors have been evaluated using the Ergonomic Risk Factor (ERF) Checklist as per SNI 9011: 2021 standards. Musculoskeletal disorders were assessed with the Nordic Body Map questionnaire, and work-related fatigue was evaluated using a reaction timer. The research analysis uses the Pearson correlation test to measure the strength and direction of the relationship between ergonomic risk and work-related fatigue, as well as between ergonomic risk and musculoskeletal disorders, with a significance threshold of p<0.05. The results indicated a positive relationship between ergonomic risk levels and the prevalence of MSDs and work-related fatigue. This suggests that higher ergonomic risks are associated with increased occurrences of musculoskeletal issues and fatigue. The findings underscore the need for targeted ergonomic interventions to mitigate these risks in pottery crafting.